2011
DOI: 10.1136/bmjopen-2010-000030
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of self-sampling and human papillomavirus testing for cervical cancer screening in First Nation women from Northwest Ontario, Canada: a pilot study

Abstract: BackgroundThe incidence of cervical cancer is up to sixfold higher among First Nation women in Canada than in the general population. This is probably due to lower participation rates in cervical cancer prevention programmes.ObjectiveTo raise screening participation in this underserved population by launching an alternative approach to (Pap)anicolaou testing in a clinic—namely, vaginal self-sampling followed by human papillomavirus (HPV) diagnostics.MethodsGood relationships were established with a First Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 29 publications
3
55
0
Order By: Relevance
“…As demonstrated in previous studies (Ogilvie et al, 2007;Zehbe et al, 2011), there is emerging evidence that self-sampling may indeed be acceptable to Aboriginal women as well as other women who were less likely to attend Pap tests in the past. The HPV self-test can be conveniently and privately administered in a woman's home, but under current health policy, this test is not financially covered by the health care system.…”
Section: Discussionmentioning
confidence: 90%
“…As demonstrated in previous studies (Ogilvie et al, 2007;Zehbe et al, 2011), there is emerging evidence that self-sampling may indeed be acceptable to Aboriginal women as well as other women who were less likely to attend Pap tests in the past. The HPV self-test can be conveniently and privately administered in a woman's home, but under current health policy, this test is not financially covered by the health care system.…”
Section: Discussionmentioning
confidence: 90%
“…This could lead to a more positive attitude towards sexual health and may have a beneficial outcome for cervical screening attendance (van Herk et al, 2010(van Herk et al, -2011. The prospects of offering self-collected vaginal samples to First Nations' women as an alternative to Pap cytology Zehbe et al, 2011), thus allowing them to conveniently take their own sample at home, was favourably acknowledged. Self-sampling for HPV would also eliminate other screening barriers such as long distance to the nearest health centre as well as lack of transportation and child care facilities (Maar et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our pilot study with one partner community has shown that close to 90% of the women would prefer self-sampling over Pap testing (Zehbe et al, 2011). For a number of HCPs interviewed, the idea of HPV testing through self-sampling was appealing and would not compromise their relationship with their patients.…”
Section: Role Of Family (Mother-daughter) Relationsmentioning
confidence: 99%
See 2 more Smart Citations